Exploring the Lipid-lowering Effects of Rosa roxburghii Tratt. Alcohol Extract on Diet-induced Obesity Rats through Hepatic Leptin Resistance Pathway - Yi SUI; Tian LU; Minggang TENG; Chaochen YUE; Li YANG; Huifang CHAI (Shipin gongye ke-ji)
Objective: To investigate the dose-dependent lipid-lowering effects of Rosa roxburghii Tratt. alcohol extract in diet-induced obese (DIO) rats and examine its regulatory mechanisms through the hepatic leptin signaling pathway. Methods: SD rats were randomly divided into a normal group, a diet-induced obesity model group, and a low- (1.25 g/kg), medium- (2.5 g/kg), and high-dose (5 g/kg) ethanol extracts group. Rats were given high-fat diet every day to create a DIO model, and a significant increase in body weight was used as a sign of successful modeling. Modeling and administration were continued for 8 weeks. The body weight of rats was measured daily, and the Lee's index of rats in each group was calculated. After the final dose administration, all rats in each group were euthanized, and their serum, liver, and adipose tissues were collected. The ELISA method was used to detect serum triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein (HDL-C), leptin (Leptin) and soluble leptin receptor (sLR) content of rats in each group. HE staining was employed to measure adipocyte cross-sectional areas in rat tissues across experimental groups. Western blot analysis quantified the protein expression levels of leptin receptor (LEPR), protein tyrosine phosphatase 1B (PTP1B/PTPN1), suppressor of cytokine signaling 3 (SOCS3), and both total and phosphorylated STAT3 (p-STAT3) in hepatic tissues from each group. Results: Different doses of Rosa roxburghii Tratt. alcohol extract significantly decreased body weight in model group rats at 5 weeks post-administration (P<0.05). By week 8, the treatment significantly lowered Lee's index, serum lipid profiles, and leptin levels in obese rats (P<0.05), with medium- and high-dose groups approaching levels observed in the normal control group. Additionally, the extract significantly elevated serum soluble leptin receptor (sLR) levels (P<0.05) and reduced white adipose tissue adipocyte cross-sectional areas (P<0.05). Western blot analysis revealed dose-dependent effects. The extract upregulated hepatic leptin receptor (LEPRb) protein expression (P<0.01), downregulated protein tyrosine phosphatase 1B (PTP1B) and suppressor of cytokine signaling 3 (SOCS3) levels (P<0.01), while enhancing phosphorylated STAT3 (p-STAT3) to total STAT3 ratios (P<0.01). Conclusion: Rosa roxburghii Tratt. alcohol extract significantly reduced body weight, Lee's index, and serum lipid levels in diet-induced obese (DIO) rats. These metabolic improvements were mediated by upregulating hepatic leptin receptor (LEPR) expression and downregulating key inhibitory factors of the leptin signaling pathway (protein tyrosine phosphatase 1B (PTP1B) and suppressor of cytokine signaling 3 (SOCS3)), thereby restoring leptin pathway sensitivity in the liver.